SUSTAINABLE URBAN DEVELOPMENT THROUGH THE LENS OF INNOVATION AND SOCIAL ENTREPRENEURSHIP - ANFILOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article presents the concept of " nerdistans", features of the stages of its evolution. The role of technology startups that are concentrated in major global cities and metros, as well as in densely populated city blocks or neighborhoods within these cities, is noted. This made it possible to argue that the city is an organizational platform for entrepreneurial activity that brings together talent, knowledge, capital and other assets that are necessary for its implementation. In the article, the author revealed the essence of the concept of "nerds" and the influence of their concentration on the development of cities. The article highlights the connection between the urban process and social entrepreneurship. The article examines examples of nerdistans: Silicon Valley, "Startup Nation" Israel, Chinese technology hubs, India - Bangalore, European technology hubs. The article systematizes the results of scientific research, in which scientists highlight the connection between social entrepreneurship and urban development and emphasize the potential of innovative development of cities as platforms for the development of entrepreneurship, guided by the coordination of urban planning and social entrepreneurship policy. This contributed to distinguishing the characteristics of three types of social entrepreneurs involved in "Bottom-up urban development" for urban development "from the bottom up". This approach is based on the use of innovation management theory and business transition management to urban planning and development research. The advantages of the implementation of the social entrepreneurship policy on the way to the sustainable development of cities and the creation of a favorable climate for the development of business in cities are highlighted. The need to develop an urban spatial policy using the concept of nerdistans and social enterprise is noted. Keywords: innovation, urban innovation, huma